Segregation analysis and floral phenotype of T2 transgenic yellow cosmos (Cosmos sulphureus Cav.) carrying neomycin phosphotransferase II gene in second generation (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Muchyiddin MGAA, Sawitri WD, Irsyadi MB, Swandari T, Purwantoro A. 2024. Segregation analysis and floral phenotype of T2 transgenic yellow cosmos (Cosmos sulphureus Cav.) carrying neomycin phosphotransferase II gene in second generation. Biodiversitas 25: 1711-1717. The seed of transgenic yellow cosmos (Cosmos sulphureus Cav.) lines harbouring neomycin phosphotranferase II (nptII) gene have been obtained from our previous studies. The nptII selectable marker gene is commonly used for developing a method to estimate the number of targeted gene integrated into the genome. In order to produce successful clones, it is important to ensure that transgenes are inherited sexually as the dominant trait in T2 progeny. This study aimed to obtain the segregation patterns of nptII gene in two populations derived from open- and self-pollinated and evaluated floral phenotypic of T2 transgenic yellow cosmos. The molecular analysis of transgenic yellow cosmos was conducted by PCR and the obtained data was analyzed using a Chi-Square test. The results showed that transgenes were inherited in 1:1 for transgenic and wild-type in both self- and open-pollinated populations. Therefore, it indicated that T2 transgenic plants were still unstable and evolved continuously to segregate independently in the over generation. Surprisingly, the morphological changes were detected in transgenic plants. The mixture of ligulate and tubular types in ray floret was found in some of the flower types in T2 yellow cosmos. In this case, nptII gene may diverge in apparently random genome insertion. This insertion would induce morphological changes in the ray floret type of flower since recombination estimates varied among transformation events.